Simulation of atmospheric motion by wind-tunnel flows: technical report - Cermak, Jack E., author; Sandborn, V. A., author; Plate, E. J., author; Binder, G. H., author; Chuang, H., author; Meroney, Robert N., author; Ito, S., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1966)
The objective of this study was to survey and compile information and experience obtained by the authors with respect to simulation of atmospheric motions by wind-tunnel flows. These notes are restricted to atmospheric phenomena in the lower 1000 m of the atmosphere as determined by the interests of the staff and the capabilities of the wind tunnels associated with the Fluid Dynamics and Diffusion Laboratory at Colorado State University.
CER66JEC-VAS-EJP-GJB-HC-RNM-SI17.
May 1966.
Keywords: Atmospheric circulation; Wind tunnels